2019
DOI: 10.3389/fphys.2019.00715
|View full text |Cite
|
Sign up to set email alerts
|

Aphidius ervi Teratocytes Release Enolase and Fatty Acid Binding Protein Through Exosomal Vesicles

Abstract: The molecular bases of the host-parasitoid interactions in the biological system Acyrthosiphon pisum (Harris) (Homoptera, Aphididae) and Aphidius ervi (Haliday) (Hymenoptera, Braconidae) have been elucidated allowing the identification of a gamma-glutamyl transpeptidase, the active component of maternal venom secretion, and teratocytes, the embryonic parasitic factors responsible for host physiology regulation after parasitization. Teratocytes, cells deriving from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…These alterations of the physiology and development of the host are essential for the survival of the offspring of the parasitoid [34]. The role of the teratocytes have been studied only in a restricted number of Braconidae and these studies have demonstrated that they can produce and often secrete a set of proteins with different characteristics and functions [35]. It is hypothesized that the factors secreted from this type of cells include inhibitors of the immune response, fungicide molecules, inhibitors of the juvenile hormone, protease, inhibitors of the phenoloxidase, molecules that block the production of ecdysteroids, and other factors that contribute to the nourishment of the parasitoid [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations of the physiology and development of the host are essential for the survival of the offspring of the parasitoid [34]. The role of the teratocytes have been studied only in a restricted number of Braconidae and these studies have demonstrated that they can produce and often secrete a set of proteins with different characteristics and functions [35]. It is hypothesized that the factors secreted from this type of cells include inhibitors of the immune response, fungicide molecules, inhibitors of the juvenile hormone, protease, inhibitors of the phenoloxidase, molecules that block the production of ecdysteroids, and other factors that contribute to the nourishment of the parasitoid [35].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the teratocytes have been studied only in a restricted number of Braconidae and these studies have demonstrated that they can produce and often secrete a set of proteins with different characteristics and functions [35]. It is hypothesized that the factors secreted from this type of cells include inhibitors of the immune response, fungicide molecules, inhibitors of the juvenile hormone, protease, inhibitors of the phenoloxidase, molecules that block the production of ecdysteroids, and other factors that contribute to the nourishment of the parasitoid [35]. Thus, teratocytes are involved in the regulation of the host to obtain nutrients from its tissues and then to provide them to the parasitoid larva for its development [36].…”
Section: Introductionmentioning
confidence: 99%
“…For their high biodiversity, with over one million described species, insects represent the largest class of organisms, with a high ability to adapt to environmental changes and high resistance to a broad spectrum of pathogens [9,10]. Insects, lacking an adaptive immune system, base their defense/survival on the production of a multitude of broadspectrum AMPs [11]; therefore, these organisms represent an essential source of biologically active compounds [12][13][14]. In particular, the dipteran Hermetia illucens, is considered an excellent model system for the identification and characterization of new AMPs since it is able to live in hostile environments rich in pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Three parasitic factors, including polydnavirus (PDVs), venom and teratocytes, have been adopted by wasps to impede the host immunity (Beckage & Gelman, 2004;Laurino et al, 2016;Salvia et al, 2017Salvia et al, , 2018Salvia et al, , 2019. Moreover, there is a further parasitic factor that must be taken into account, ovarian proteins (Salvia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%